XEBPER: an E-book using Java 3D API - N, Hameed; N, Yu-; M., Rafie, (Malaysian Journal of Computer Science, 2011)
This paper presents visual layout using 2D/3D perspectives for e-book personalization and building methodology. E-book visualization is being shown by interpreting book metaphors in computer display devices. It can be expressed with advanced features such as hyper-linking, note-taking, highlights, bookmarks, etc. It does not contain enough things for representation and layout procedures, especially including the advance technique for rendering methods. E-book modeling includes the personalization structure with 3D modeling using Java 3D API. This model consists of four main components such as structural, processing, layout and stimulus functions. Structural component presents for utilizing XEBPER, an acronym for eXtensible E-Book Personalization structure. Processing is implementing with Java 3D system. Layout component enhances rendering methods by including virtual reality techniques using 2D/3D modeling techniques. Stimulus function component causes perfect connection between features and events. It establishes the capabilities for describing virtual reality about an e-book phenomenon, animating an e-book in real environment. Experiment analysis is carried out for evaluating e-book personalization feature. Thus survey reporting also concluded as XEBPER is more suitable for personalizing and browsing e-book structure contents.